Cytotoxic effects of extracts and isolated compounds from Ifloga spicata (forssk.) sch. bip against HepG-2 cancer cell line: Supported by ADMET analysis and molecular docking - Hussain, Sajid; Liufang, He; Shah, Syed Majid; Ali, Fawad; Khan, Saeed Ahmad; Shah, Fawad Ali; Li, Jing Bo; Li, Shupeng (Frontiers in Pharmacology, 2022)
The purpose of this study was to determine the anticancer potential of Ifloga spicata (I. spicata) against HepG-2 cell line. To assess I. spicata cytoxicity, brine shrimp lethality and MTT assays were performed. In the brine shrimp bioassay, the ethyl acetate fraction had a significant impact with an IC50 of 10 µg/mL. The ethyl acetate and chloroform fractions inhibited HepG-2 cell line effectively (IC50 values 5.54 and 6.52 µg/mL, respectively). The isolated compound, heptadecyl benzoate inhibited growth significantly (IC50, 8.92 µg /mL) while methyl dihydroxybenzoate had modest activity (25.66 µg /mL) against the cell line. Both compounds displayed acceptable pharmacokinetic parameters in the ADME study. In the docking study, the methyl dihydroxybenzoate was involved in two hydrogen bonds with two different residues Thr830 and Asp831. The heptadecyl benzoate carbonyl oxygen exhibited a single hydrogen bond with Lys692. Both showed good interactions with the active site of the (EGFR) tyrosine kinase. Our findings suggest that I. spicata might be a viable source of anticancer natural agents. This discovery raises the prospect of the future development of a new medication for the treatment of liver cancer.